Efficient Transdermal Delivery of Benfotiamine in an Animal Model - Gyula Varadi; Zhen Zhu; Stephen G. Carter (International Association of Physical Chemists (IAPC), 2015)
We designed a transdermal system to serve as a delivery platform for benfotiamine utilizing the attributes of passive penetration enhancing molecules to penetrate through the outer layers of skin combined with the advance of incorporating various peripherally-acting vasodilators to enhance drug uptake.  Benfotiamine, incorporated into this transdermal formulation, was applied to skin in an animal model in order to determine the ability to deliver this thiamine pro-drug effectively to the sub-epithelial layers.  In this proof of concept study in guinea pigs, we found that a single topical application of either a solubilized form of benfotiamine (15 mg) or a microcrystalline suspension form (25 mg) resulted in considerable increases of the dephosphorylated benfotiamine (S-benzoylthiamine) in the skin tissue as well as in significant increases in the thiamine and thiamine phosphate pools compared to control animals.  The presence of a ~8000x increase in thiamine and increases in its phosphorylated derivatives in the epidermis and dermis tissue of the test animals gives a strong indication that the topical treatment with benfotiamine works very well for the desired outcome of producing an intracellular increase of the activating cofactor pool for transketolase enzyme, which is implicated in the pathophysiology of diabetic neuropathy.